Nivel de conocimiento y conductas promotoras de salud en estudiantes de enfermería técnica. Consorcio San Luis – Trujillo, 2018 - Paez Escobedo, Katherinne Lisset (2019)
ABSTRACT This correlational descriptive research study was carried out in Trujillo, with the purpose of identifying if there is a relationship between level of knowledge and health promoting behaviors in students of technical nursing of the San Luis Consortium, in the months of August to December of 2018. The sample universe consisted of 30 nursing technical students, the data was automatically processed in a computer system using statistical test, reaching the following conclusion, 56.7% of students have a high level of knowledge, 33.3% of students present level of regular knowledge, and 10% of student presented low level of knowledge about health promoting behaviors, thus 70% of students have healthy promoter behaviors and 30% unhealthy promoter behaviors. Being the value of chi-square 13.6 with probability 0.001 being highly significant, so there is a relationship between level of knowledge and promoting behavior in students of technical nursing at the San Luis Consortium.